DESIGNING FOR ERGONOMIC GAWANGAN BY USING A ROLLER - Novrianti; Chandra Dewi, Diana; Handayani, Corry; Bayhaqi, Imam (Indonesian Society of Applied Science, 2024)
Batik craftsmen needed a tool to help them while writing on the carving fabric (covering the motif on the fabric) with wax. They use gawangan for buffering the writing fabric for the sake of the easiest way for the writing process and the fabric is not folded. This is because if the fabric is pleated, the wax on the fabric will harden, break off, and come off the fabric. For this long time, the craftsmen still used the wooden gawangan, and only wrote a unit of batik once a time in the production process. The main problem is how to make the fabric after the wax process saving safely. Gawangan that using roller is a kind of innovation that has never been made before, in Jambi, moreover in Indonesia or maybe in the world. The dimension of the design will use anthropometric data so that the gawangan is ergonomic. The main purpose of this design is to ensure that the fabric that has been long waxed is safe, without any anxiety about the motif on the fabric breaking due to broken wax. Further, this gawangan is designed to accommodate rolls of fabric up to 100 meters.